Lithium nickel-based composite oxides as positive electrode active materials for rechargeable lithium-ion batteries
The positive electrode active material, comprising specific proportions of Li, Ni, Co, Mn, and Zr, addresses the challenge of achieving a high initial charging capacity in solid-state batteries, thereby improving energy storage efficiency for electric vehicles and hybrid electric vehicles.
Patent Information
- Application Number
- JP2023551773
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-02-25
- Filing Date
- 2022-02-24
- Publication Date
- 2025-04-30
- Estimated Expiration
- 2042-02-24
AI Technical Summary
Existing positive electrode active materials for solid-state batteries struggle to achieve an initial charging capacity of 160 mAh/g or more, which is essential for efficient energy storage in electric vehicles and hybrid electric vehicles.
A positive electrode active material comprising Li, M', and oxygen, where M' is Ni with a content of 50.0mol% to 75.0mol%, Co with a content of 0.0mol% to 40.0mol%, Mn with a content of 0.0mol% to 40.0mol%, and includes Zr with a content of 0.1 mol% to 5.0 mol%. The material has a specific Zr content ratio and primary particle size range, optimized for improved electrochemical performance.
The optimized positive electrode active material achieves an initial charging capacity of 160 mAh/g or more, enhancing the energy storage efficiency and performance of solid-state batteries for electric vehicles and hybrid electric vehicles.
Smart Images

Figure 0007670846000006 
Figure 0007670846000007 
Figure 0007670846000008
Abstract
Description
[Technical field]
[0001] The present invention relates to a lithium nickel-based oxide positive electrode active material for solid-state batteries suitable for electric vehicle (EV) and hybrid electric vehicle (HEV) applications, comprising lithium nickel-based oxide particles containing zirconium (Zr). [Background technology]
[0002] The positive electrode active material is defined as a material that is electrochemically active in the positive electrode, which is understood to be a material that can capture and release Li-ions when exposed to a voltage change for a certain period of time.
[0003] In the framework of the present invention, atomic % means atomic percentage. Atomic % or "atom percent" as an expression of the concentration of a given element means what percentage of all atoms in the claimed compound are atoms of that element. The term atomic % is synonymous with mol % or "mol percent".
[0004] The weight percentage (wt%) of the first element E in the material (E wt1 ) can be calculated for a given atomic percent (atomic %) of the first element E in the material by applying the formula: at1 ) can be converted from the formula: at1 and E aw1 (E aw1 is the atomic weight (or molecular weight) of the first element E, and the product of E ati ×E awi where n is an integer representing the number of different elements contained in the material.
[0005]
number
[0006] An object of the present invention is to provide a positive electrode active material having an improved first charge capacity of 160 mAh / g or more in a solid-state battery. [Means for solving the problem]
[0007] The object is to provide a cathode active material for a solid-state battery, the cathode active material comprising Li, M' and oxygen, M' being Ni with a content x of 50.0 mol% to 75.0 mol% relative to M'; Co with a content y of 0.0 mol% to 40.0 mol% relative to M'; Mn with a content z of 0.0 mol% to 40.0 mol% relative to M'; D having a content a of 0.0 mol% to 2.0 mol% relative to the total atomic content of M', and containing at least one element selected from the group consisting of Al, B, Ba, Ca, Cr, Fe, Mg, Mo, Nb, S, Si, Sr, Ti, Y, V, W and Zn; and Zr having a content b of 0.1 mol% to 5.0 mol% relative to M'; x, y, z, a, and b are measured by ICP; x+y+z+a+b is 100.0 mol%, The positive electrode active material has a Zr content defined as b / (x+y+z+b) A The positive electrode active material has a Zr content of Zr B and Zr B was determined by XPS analysis, and Zr B is expressed as a mole fraction compared to the sum of the mole fractions of Co, Mn, Ni and Zr as determined by XPS analysis, Zr ratio B / Zr A >50.0, The positive electrode active material includes secondary particles having a plurality of primary particles, The primary particles are achieved by providing a cathode active material having an average diameter of 170 nm to 340 nm as determined by the method of the present invention.
[0008] The present invention relates to the following embodiments.
[0009] EMBODIMENT 1 In a first aspect, the present invention provides a cathode active material for a solid-state battery, the cathode active material comprising Li, M′, and oxygen, wherein M′ is Ni with a content x of 50.0 mol% to 75.0 mol% relative to M'; Co with a content y of 0.0 mol% to 40.0 mol% relative to M'; Mn with a content z of 0.0 mol% to 70.0 mol% relative to M', preferably Mn with a content z of 0.0 mol% to 40.0 mol% relative to M'; D having a content a of 0.0 mol% to 2.0 mol% relative to the total atomic content of M', and containing at least one element selected from the group consisting of Al, B, Ba, Ca, Cr, Fe, Mg, Mo, Nb, S, Si, Sr, Ti, Y, V, W and Zn; Zr having a content b of 0.1 mol% to 5.0 mol% relative to M'; x, y, z, a, and b are measured by ICP; x+y+z+a+b is 100.0 mol%, The positive electrode active material has a Zr content defined as b / (x+y+z+b) A The positive electrode active material has a Zr content of Zr B and Zr B was determined by XPS analysis, and Zr B is expressed as a mole fraction in percent compared to the sum of the mole fractions of Co, Mn, Ni and Zr as determined by XPS analysis, and the ratio Zr B / Zr A >50.0.
[0010] Zr ANote that Zr content of the positive electrode active material as determined by ICP, expressed as a fraction of the sum of the Co, Ni, Mn and Zr contents.
[0011] Preferably, Zr B / Zr A The ratio is 80 or more, preferably 100 or more, and more preferably 130 or more. B / Zr A The ratio is 500 or less, more preferably 300 or less, and most preferably 200 or less.
[0012] Preferably, the positive electrode active material comprises secondary particles having a plurality of primary particles, the primary particles having an average diameter of 170 nm to 340 nm, preferably 200 nm to 340 nm, as determined by measuring the primary particle size in an image taken by SEM.
[0013] More preferably, the primary particles have an average diameter of 180 nm or more, preferably 200 nm or more, preferably 220 nm or more, even more preferably 225 nm or more.
[0014] Preferably, the primary particles have an average diameter of less than or equal to 330 nm, preferably less than or equal to 320 nm, more preferably less than or equal to 300 nm, even more preferably less than or equal to 250 nm.
[0015] Preferably, the primary particles have an average diameter of 180 nm to 330 nm, preferably 200 nm to 320 nm, more preferably 220 nm to 310 nm, even more preferably 225 nm to 250 nm.
[0016] As will be appreciated by those skilled in the art, primary particle size is determined by measuring the particle size of the primary particles in an image taken by SEM.
[0017] Preferably, x≧55.0 mol%, more preferably x≧60.0 mol%.
[0018] Preferably, y > 0 mol%, more preferably y ≧ 5.0 mol, and even more preferably y ≧ 10.0 mol%.
[0019] In another embodiment, the Ni with content x is 55 mol% to 72 mol% with respect to M', and the Co with content y is 0.0 mol% to 20.0 mol% with respect to M'.
[0020] In a preferred embodiment, Ni has a content of x ≧ 55.0 mol%, preferably x ≧ 60.0 mol%, and more preferably x ≧ 62.0 mol%. In a preferred embodiment, x ≦ 72.0 mol%, preferably x ≦ 70.0 mol%, and more preferably x ≦ 68.0 mol%.
[0021] In a more preferred embodiment, Ni has a content x of 55.0 mol% ≦ x ≦ 72.0 mol%, preferably 60.0 mol% ≦ x ≦ 70.0 mol%, and more preferably 62.0 mol% ≦ x ≦ 68.0 mol%.
[0022] As will be understood by those skilled in the art, the amounts of Li and M' in the positive electrode active material, preferably Li, Ni, Mn, Co, D, and Zr, are measured by inductively coupled plasma-optical emission spectroscopy (ICP-OES). For example, without limiting the present invention, Agilent ICP 720-ES is used in ICP-OES analysis.
[0023] In a preferred embodiment, Mn has a content of z > 0.0 mol%, more preferably z ≧ 5.0 mol%, and even more preferably z ≧ 8.0 mol%. In a preferred embodiment, the content is z ≦ 40.0 mol%, preferably z ≦ 30.0 mol%, and more preferably z ≦ 25.0 mol%. In a preferred embodiment, the content is 0.0 mol% < z ≦ 40.0 mol%, preferably 5.0 mol% ≦ z ≦ 30.0 mol%, and more preferably 8.0 mol% ≦ z ≦ 25.0 mol%.
[0024] In a preferred embodiment, Co has a content of y > 0.0 mol%, more preferably y ≧ 1.0 mol%, still more preferably y ≧ 3.0 mol%. In a preferred embodiment, the content is y ≦ 40.0 mol%, more preferably y ≦ 30.0 mol%, still more preferably y ≦ 25.0 mol%. In a preferred embodiment, the content is 0.0 mol% < y ≦ 40.0 mol%, preferably 1.0 mol% ≦ y ≦ 30.0 mol%, more preferably 3.0 mol% ≦ y ≦ 25.0 mol%.
[0025] In a preferred embodiment, D contains at least one element selected from the group consisting of Al, B, Ba, Ca, Cr, Fe, Mg, Mo, Nb, S, Si, Sr, Ti, Y, V, W, and Zn, preferably Al, B, Cr, Nb, S, Si, Ti, Y, and W.
[0026] In a preferred embodiment, D has a content of a > 0.0 mol%, more preferably a ≧ 0.25 mol%, still more preferably a ≧ 0.5 mol%. In a preferred embodiment, the content is a ≦ 2.0 mol%, preferably a ≦ 1.75 mol%, more preferably a ≦ 1.5 mol%. In a preferred embodiment, the content is 0.0 mol% < a ≦ 2.0 mol%, preferably 0.25 mol% ≦ a ≦ 1.75 mol%, more preferably 0.5 mol% ≦ a ≦ 1.5 mol%.
[0027] As will be understood by those skilled in the art, the secondary particles contain a plurality of primary particles, preferably more than 20 primary particles, preferably more than 10 primary particles, and most preferably more than 5 primary particles. A primary particle is an individual crystal or a particle formed from primary particles, each of which is an individual crystal and has less than 5, preferably 3 or less, such individual crystals. This can be seen by observing the grain boundaries with an appropriate microscopy technique such as a Scanning Electron Microscope (SEM).
[0028] Embodiment 2 In a second embodiment, preferably according to Embodiment 1, the Zr content ZrA is b / (b+x+y+z) and is 0.10 mol% or more and 1.00 mol% or less. Preferably, the Zr content Zr A is b / (b+x+y+z) and is 0.20 mol% or more and 0.80 mol% or less. Most preferably, the Zr content Zr A is b / (b+x+y+z) and is equal to or greater than 0.30 mol% and equal to or less than 0.70 mol%. In an alternative but more preferred embodiment, the Zr content Zr A is b / (b+x+y+z) and is 0.10 mol% or more and 1.50 mol% or less. Preferably, the Zr content Zr A is b / (b+x+y+z) and is 0.20 mol% or more and 1.00 mol% or less. Most preferably, the Zr content Zr A is b / (b+x+y+z) and is 0.30 mol% or more and 0.90 mol% or less.
[0029] In a preferred embodiment, Zr has a content b of 0.10 mol % or more and 1.00 mol % or less with respect to M', more preferably 0.20 mol % or more and 0.80 mol % or less with respect to M', and most preferably 0.30 mol % or more and 0.70 mol % or less with respect to M'.
[0030] In an alternative but still more preferred embodiment, Zr has a content b of ≧0.10 mol % and ≦1.50 mol % relative to M′, more preferably ≧0.20 mol % and ≦1.00 mol % relative to M′, and most preferably ≧0.30 mol % and ≦0.90 mol % relative to M′.
[0031] In a preferred embodiment, the Zr content is Zr B is greater than 0.25 mol%, preferably greater than 0.50 mol%, and most preferably greater than 0.60 mol%. In a preferred embodiment, Zr B is less than 2.0 mol%, preferably less than 1.5 mol%, more preferably less than 1.0 mol%. In a preferred embodiment, Zr Bis 0.25 mol% to 2.0 mol%, preferably 0.50 mol% to 1.5 mol%, and most preferably 0.60 mol% to 1.0 mol%. As will be understood by those skilled in the art, Zr B is expressed as the mole fraction determined by XPS analysis compared to the sum of the mole fractions of Co, Mn, Ni and Zr determined by XPS analysis.
[0032] EMBODIMENT 3 In a third embodiment according to embodiment 1 or 2, the material has a median secondary particle size D50, as determined by laser diffraction particle size analysis, of 2 μm or more, preferably 5 μm or more.
[0033] Preferably the material has a median secondary particle size D50 of 15 μm or less, preferably 13 μm or less, as determined by laser diffraction particle size analysis.
[0034] For example, and not by way of limitation, laser diffraction particle size analysis is performed on a Malvern Mastersizer 3000.
[0035] EMBODIMENT 4 In a fourth embodiment according to embodiments 1 to 3, the material has a carbon content, as determined by a carbon analyzer, of 600 ppm or more, preferably 650 ppm or more, more preferably 750 ppm or more, and most preferably 900 ppm or more.
[0036] Preferably, the material has a carbon content of 5000 ppm or less, preferably 3000 ppm or less, more preferably 1500 ppm or less, and most preferably 1100 ppm or less, as determined by a carbon analyzer.
[0037] EMBODIMENT 5 In a fifth embodiment according to any one of the first to fourth embodiments, the thickness of Zr is greater than 10 nm. Preferably, the thickness is 15 nm or more, more preferably 20 nm or more, as determined by TEM-EDS measurement. Preferably, the thickness of Zr is 100 nm or less, preferably, the thickness is 50 nm or less, more preferably, the thickness is 30 nm or less. Preferably, the thickness of Zr is 10 nm to 100 nm, preferably, 15 nm to 50 nm, more preferably, 22 nm to 28 nm.
[0038] In the framework of the present invention, the (minimum) thickness of the surface layer is defined as the shortest distance between a first point located on the periphery of the cross section of the particle and a second point located on a line defined between said first point and the geometric center (or center of gravity) of said particle, and the position of the second point (Zr 2 ) and the difference in Zr content measured at any location between the location of the second point and the center of the particle is approximately 0.1 atomic %.
[0039] The Zr content at the position of the second point (Zr 2 ) is constant and may be greater than 0 atomic percent, and the first content of Zr at the position of the first point (Zr 1 ) must be less than 5.0%. 2 The second content of Zr is the Zr content at the position of the third point of the line (Zr 3 ) and the third point is located at any position between the geometric center of the particle and the position of the second point.
[0040] In other words, the thickness of the surface layer corresponds to a minimum distance D defined as follows: D (in nm) = L Zr1 -L Zr2 L Zr1 is the position of the first point on the periphery of the particle, and L Zr2 is the position of a second point on a line defined between the position of the first point and the geometric center of the particle, as shown in FIG. Second point location L Zr2The second content of Zr measured by TEM-EDS at is 0 atomic % or more and is greater than the first content of Zr measured at the position of the first point (Zr 1 ) is 5.0% or less. 2 ) is defined as follows: Zr 2 (unit: atomic %) = Zr 3 ±0.1 atomic % and, optionally, Zr 1 -Zr 2 ≧10.0 atomic% Zr 3 is the position of the third point of the line (L Zr3 ) the third content (in atomic percent) of Zr in the grain, and the third point is a point between the geometric center of the grain and the position L of the second point. Zr2 It is located anywhere between.
[0041] Zr 2 and Zr 3 is greater than 0.0 atomic %, the second and third contents of Zr correspond to the contents of Zr present as dopant in the core of the particles according to the invention, as determined by TEM-EDS.
[0042] The TEM-EDS protocol is applied as follows. 1) Cross-sectional TEM lamellae of lithium transition metal-based oxide particles are extracted by cutting the particle samples using a Ga ion beam to obtain the prepared samples. 2) The prepared samples (particle cross-sections) are scanned by TEM / EDS line scan from the outer edge of the surface layer to the center of the lithium transition metal-based oxide particles to provide quantitative elemental analysis of the cross-sections. 3) The Zr content detected by EDS is normalized by the total atomic content of Ni, Mn, Co and Zr in the scanned lamella. 4) The measured line scan of Zr / (Ni+Mn+Co+Zr) is then plotted as a function of linear distance across the cross section of the particle.
[0043] The above steps 1) to 4) are repeated the same number of times as the number of particles to be analyzed.
[0044] The aforementioned TEM-EDS measurements are performed on at least one grain. If more than one grain is measured, Zr / (Ni+Mn+Co+Zr) is numerically averaged.
[0045] For example, and not by way of limitation, TEM-EDS measurements were performed using a Tecnai G detector equipped with an ELITE T 70 detector (EDAX). 2 This is carried out using an F30 S-TWIN (FEI).
[0046] As will be understood by those skilled in the art, in any of the first to fifth embodiments, Zr B is expressed as the mole fraction determined by XPS analysis compared to the sum of the mole fractions of Co, Mn, Ni, and Zr determined by XPS analysis. B is the mole fraction of Zr measured in a region of a secondary particle of the positive electrode active material according to the present invention, defined between a first point on the outer edge of the particle and a second point at a certain distance from the first point, the distance separating the first point and the second point being equal to the XPS penetration depth, D being 1.0 to 10.0 nm. In particular, the penetration depth is the distance along an axis perpendicular to a virtual line tangent to the outer edge and passing through the first point.
[0047] The outer edge of a particle is, within the framework of the present invention, the boundary or outer limit which distinguishes the particle from its external environment.
[0048] Thus, the XPS analysis provides the atomic content of the element in the top layer of the particle with a penetration depth of about 10.0 nm from the periphery of the particle. The periphery of the particle is also called the "surface". In the framework of the present invention, atomic % means atomic percentage. Atomic % or "atomic percent" as a concentration expression of a given element means what percentage of all atoms in the compound are atoms of that element. The term atomic % is synonymous with mol % or "mole percent". For example, and without limiting the present invention, the XPS analysis is performed using a Thermo K-α+ spectrometer (Thermo Scientific).
[0049] The present invention relates to the use of the positive electrode active material according to any one of the above-mentioned embodiments 1 to 5 in a battery.
[0050] The present invention also provides a method for producing a positive electrode active material according to any one of the above-mentioned embodiments 1 to 5, Preparing a lithium transition metal based compound; mixing the lithium transition metal based compound with a Zr source, preferably a Zr alkoxide in a lithium alkoxide-containing alcoholic solvent, thereby obtaining a mixture; removing the volatile phase, including the solvent, preferably by vacuum heating; and heating the mixture at a temperature of 350° C. or more and less than 500° C., preferably 450° C. or less, in an oxidizing atmosphere in a furnace for a period of 1 hour to 20 hours to obtain the positive electrode active material powder according to the present invention.
[0051] In a preferred embodiment, the lithium transition metal based compound is a lithium nickel based oxide compound.
[0052] In a preferred embodiment of the method, the lithium transition metal based oxide compound comprises Li, M' and oxygen, where M' comprises Ni, Mn, Co and D, where D is at least one element from the group consisting of Al, B, Ba, Ca, Cr, Fe, Mg, Mo, Nb, S, Si, Sr, Ti, Y, V, W and Zn; preferably, Al, B, Cr, Nb, S, Si, Ti, Y, W.
[0053] Preferably, the lithium transition metal oxide powders used are also typically prepared according to a lithiation process, i.e. a process in which a mixture of a transition metal precursor and a lithium source is heated, preferably at a temperature of 500° C. or higher. Typically, the transition metal precursor is prepared by co-precipitation of one or more transition metal sources, such as salts, preferably sulfates, of the M′ elements Ni, Mn and / or Co, in the presence of an alkali compound, such as an alkali hydroxide, for example sodium hydroxide and / or ammonia.
[0054] Preferably, the method comprises the further step of drying the mixture, preferably by vacuum heating, prior to heating the mixture.
[0055] In a preferred embodiment of the method, the Zr source is a Zr alkoxide, preferably Zr ethoxide, Zr propoxide or Zr butoxide, more preferably Zr propoxide. In a preferred embodiment, the Zr alkoxide is mixed with the mixture as a solid. Alternatively, more preferably, the Zr alkoxide is mixed with the slurry as a solution, the solution comprising Zr alkoxide and a further alcohol, the alkoxide group being the conjugate base of the further alcohol. For example, the Zr alkoxide is Zr propoxide dissolved in propanol. Typically, the solution comprises 50-90 wt% Zr alkoxide of the total weight of the solution. Examples of such solutions are 70 wt% Zr propoxide in 1-propanol, or 80 wt% Zr butoxide in 1-butanol.
[0056] Preferably, the alcohol solvent is methanol, ethanol, propanol or butanol, preferably ethanol.
[0057] The present invention also includes a solid-state battery including the positive electrode active material according to any one of the above-mentioned embodiments 1 to 5, and preferably, the solid-state battery includes a sulfide-based solid electrolyte, more preferably, the sulfide-based solid electrolyte includes Li, P, and S. Typically, the following sulfur-containing compounds are included: Li 6 P.S. 5Cl(LPSCL), thio-LISICON (Li 3.25 Ge 0.25 P 0.75 S 4 ), Li 2 S-P 2 S 5 -LiCl, LiC 2 S-SiS 2 , LiI-Li 2 S-SiS 2 , Li-P 2 S 5 -LiCl, LiC 2 S-SiS 2 , LiI-Li 2 S-SiS 2 , LiI-Li 2 , LiI-Li 2 S 5 , LiI-Li 2 SP 2 O 5 , LiI-Li 3 PO 4 -P 2 S 5 , Li 2 S-P 2 S 5 , Li 3 PS 4 , Li 7 P 3 S 11 , LiI-Li 2 , LiI-Li 2 S 3 , Li 3 PO 4 -Li 2 S-SiS 2 , Li 3 PO 4 Li 2 S-SiS 2、 LiPO 4 -Li 2 S-SiS 2 , Li 10 GeP 2 S 12 , Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3 and / or Li 7 P 3 S 11can be preferably used. [Brief description of the drawings]
[0058] [Figure 1a] The SEM image shows the secondary particles of Comparative Example 2.2 containing multiple primary particles. The dotted line indicates the area that was captured to obtain the average primary particle diameter. [Figure 1b] SEM image of Comparative Example 2.2 to obtain the average primary particle diameter. [Figure 1c] SEM image of Example 1 to obtain the average primary particle diameter. [Diagram 2] 1 shows XPS spectra showing Zr peaks for Example 1 and Comparative Example 2.2. [Diagram 3] TEM-EDS analysis results of Zr / (Ni+Mn+Co+Zr) in Example 1 (x-axis: distance from the start of the surface layer at 0, y-axis: elements in atomic ratio). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0059] To enable the practice of the invention, preferred embodiments are described in the drawings and the following detailed description. Although the invention has been described with reference to these specific preferred embodiments, it will be understood that the invention is not limited to these preferred embodiments. The invention includes numerous alternatives, modifications, and equivalents that will be apparent from consideration of the following detailed description and the accompanying drawings.
[0060] A) ICP analysis The amount of Li, Ni, Mn, Co and Zr in the positive electrode active material powder is measured using an inductively coupled plasma (ICP) method by using an Agilent ICP 720-ES (Agilent Technologies) (https: / / www.agilent.com / cs / library / brochures / 5990-6497EN%20720-725_ICP-OES_LR.pdf). Two grams of powder sample is dissolved in 10 mL of high-purity hydrochloric acid (more than 37 wt% HCl relative to the total weight of the solution) in an Erlenmeyer flask. The flask is covered with glass and heated on a hot plate at 380 °C until the precursor is completely dissolved. After cooling to room temperature, the solution in the Erlenmeyer flask is poured into a 250 mL volumetric flask. Then, the volumetric flask is filled with deionized water up to the 250 mL mark, followed by complete homogenization. Pipette out an appropriate amount of the solution and transfer it to a 250 mL volumetric flask for the second dilution, fill the volumetric flask up to the 250 mL mark with the internal standard and 10% hydrochloric acid, then homogenize. Finally, use this 50 mL solution for ICP measurement.
[0061] B) SEM (scanning electron microscope) analysis The morphology of the positive electrode active material is analyzed by scanning electron microscopy (SEM) technique. The measurements were performed using a JEOL JSM 7100F (https: / / www.jeolbenelux.com / JEOL-BV-News / jsm-7100f-thermal-field-emission-electron-microscope) at 25 °C with a resolution of 9.6 × 10 -5 The experiment is carried out in a high vacuum environment of 100 Pa.
[0062] C) Particle size C1) Secondary particle size analysis The particle size distribution (PSD) of the cathode active material powders is measured by laser diffraction particle size analysis using a Malvern Mastersizer 3000 equipped with a Hydro MV wet dispersion accessory (https: / / www.malvernpanalytical.com / en / products / product-range / mastersizer-range / mastersizer-3000#overview) after dispersing each powder sample in an aqueous medium. Sufficient ultrasonic irradiation and stirring are applied and appropriate surfactants are introduced to improve the dispersion of the powders. D50 is defined as the particle size at 50% of the cumulative volume percent distribution obtained from the Malvern Mastersizer 3000 by Hydro MV measurement.
[0063] C2) Primary particle size analysis The diameter of the primary particles is calculated by using ImageJ software (ImageJ 1.52a, National Institutes of Health, USA) according to the following steps. Step 1) Open a file containing an SEM image of the positive electrode active material taken at the center of a secondary particle at a magnification of 10,000 times. An example of such an image is shown in Figure 1a, where the dotted line indicates the captured area corresponding to Figure 1b. Step 2) Set the scale according to the SEM magnification. Step 3) For at least 50 particles, use the polygon selection tool to draw a line along the edge of the primary particles. Particles at the edge of the image are excluded if they are truncated. Step 4) Measure the area of the selected, drawn primary particle using the measurement settings and area box. Step 5) Calculate the particle diameter from each measured area according to d=2×√(area / π) by assuming the particles to be spherical; The average primary particle diameter is obtained for at least 50 particles.
[0064] D) X-ray photoelectron spectroscopy In the present invention, X-ray photoelectron spectroscopy (XPS) is used to analyze the surface of the positive electrode active material powder particles. In the XPS measurement, the signal is obtained from the top of the sample, i.e., the first few nanometers (e.g., 1 nm to 10 nm) of the surface layer. Therefore, all elements measured by XPS are contained in the surface layer.
[0065] For the surface analysis of the positive electrode active material powder particles, XPS measurements are performed using a Thermo K-α+ spectrometer (Thermo Scientific, https: / / www.thermofisher.com / order / catalog / product / IQLAADGAAFFACVMAHV).
[0066] Monochromatic Al Kα radiation (hυ=1486.6 eV) is used with a spot size of 400 μm and a measurement angle of 45°. An extensive survey scan to identify the elements present at the surface is performed with a pass energy of 200 eV. The C1s peak with maximum intensity (or center) at a binding energy of 284.8 eV is used as the calibration peak position after data collection.
[0067] Then, for each identified element, at least 10 precise narrow scans at 50 eV are performed to determine the exact surface composition.
[0068] Curve fitting is performed with CasaXPS version 2.3.19PR1.0 (Casa Software) (http: / / www.casaxps.com / ) using Shirley-type background processing and Scofield sensitivity coefficients. Fitting parameters are according to Table 1. The lineshape GL(30) is a Gaussian / Lorentzian product formula with a 70% Gaussian line and a 30% Lorentzian line. LA(α,β,m) is the asymmetric lineshape, where α and β define the tail broadening of the peak and m defines the width.
[0069] [Table 1]
[0070] For the Zr and Co peaks, limits are set for the respective defined peaks according to Table 2.
[0071] [Table 2]
[0072] The surface content of Zr determined by XPS is expressed as the mole fraction of Zr in the surface layer of a particle divided by the total content of Ni, Mn, Co and Zr in that surface layer, which is calculated as follows: Fraction of Zr = Zr B =Zr(atomic%) / (Ni(atomic%)+Mn(atomic%)+Co(atomic%)+Zr(atomic%))
[0073] E) Sulfide solid-state battery testing E1) Preparation of sulfide solid-state battery Preparation of the positive electrode: For the preparation of the positive electrode, a slurry containing the positive electrode active material powder, Li-PS based solid electrolyte, carbon (Super-P, Timcal), and binder (RC-10, Arkema) in a ratio of 64.0:30.0:3.0:3.0 by weight in butyl acetate solvent is mixed in an Ar-filled glove box. The slurry is cast onto one side of an aluminum foil, and the slurry-coated foil is subsequently dried in a vacuum oven to obtain the positive electrode.
[0074] The obtained positive electrode was punched out to a diameter of 10 nm, where the amount of active material carried was approximately 4 mg / cm 2 It is.
[0075] Preparation of the negative electrode: For preparation of the negative electrode, a Li foil (diameter 3 mm, thickness 100 μm) is centered on top of an In foil (diameter 10 nm, thickness 100 μm) and pressed to form a Li-In alloy negative electrode.
[0076] Separator For the preparation of the separator, which also functions as a solid electrolyte in the battery, the Li-PS-based solid electrolyte is pelletized under a pressure of 250 MPa to obtain a pellet thickness of 100 μm.
[0077] Cell assembly The sulfide solid-state battery is assembled in an argon-filled glove box from bottom to top in the following order: cathode with Al current collector with coated part on top - separator - anode with Li side up - Cu current collector. The stacked components are pressed together at a pressure of 250 MPa and placed in an external cage to prevent air exposure.
[0078] E2) Test method The test method is a conventional "constant cut-off voltage" test. Conventional cell testing of the present invention follows the schedule shown in Table 3. Each cell is cycled at 60°C using a Toscat-3100 computer-controlled galvanostatic cycling station (Toyo). The schedule uses a 1C current definition of 160mA / g. The initial charge capacity (CQ1) and discharge capacity (DQ1) are measured in constant current mode (CC) at a C-rate of 0.1C over the following voltage ranges: - For Comparative Example 1.1, Example 1, Comparative Example 2.1, Comparative Example 2.2, Comparative Example 3 and Example 2, 4.2V to 2.5V (Li / Li + ) or 3.6V~1.9V(InLi / Li + ).
[0079] The irreversible capacity IRRQ is expressed as a percentage as follows: IRRQ(%)=(CQ1-DQ1)×100 / CQ1
[0080] [Table 3]
[0081] F) TEM (Transmission Electron Microscope) Analysis To investigate the Zr distribution within the lithium transition metal oxide particles, cross-sectional TEM lamellae of the particles are prepared by a Nova Nano SEM200 (FEI). A Ga ion beam is used at a voltage of 30 kV and a current of 30 pA to 7 nA. The dimensions of the obtained etched samples are 5 × 8 μm and 100 nm thick. Using the prepared (etched) samples, the surface characteristics from the top to the center of the lithium transition metal oxide particles are analyzed by TEM and energy-dispersive X-ray spectroscopy (EDS). TEM-EDS line scans are performed using a Tecnai G with an ELITE T 70 detector (EDAX). 2 The EDS analysis of the lithium transition metal oxide particles provides a quantitative elemental analysis of the cross section. The Zr content is normalized by the total atomic fraction of Ni, Mn, Co and Zr.
[0082] The invention is further illustrated by the following (non-limiting) examples.
[0083] Comparative Example 1 Comparative Example 1 is obtained by a solid-state reaction between a lithium source and a transition metal-based source, which is carried out as follows. 1) Coprecipitation: The metal composition Ni was obtained by a coprecipitation process in a large continuous stirred tank reactor (CSTR) containing mixed nickel-manganese-cobalt sulfate, sodium hydroxide, and ammonia. 0.64 Mn 0.17 Co 0.20 A transition metal oxide hydroxide precursor having the formula: 2) Mixing: A transition metal-based oxide hydroxide precursor and LiOH as a lithium source are homogeneously mixed in an industrial blending device with a lithium to metal M' (Li / M') ratio of 1.03 to obtain a mixture. 3) First heating: The mixture from step 2) is heated under oxygen atmosphere at 830° C. for 10 hours. The heated powder is crushed, classified and sieved to obtain an intermediate product. 4) Second heating: The intermediate product from step 3) is heated at 350°C for 6 hours under oxygen atmosphere to obtain Comparative Example 1.1 having M' containing Ni, Mn and Co with Ni:Mn:Co ratio of 0.638:0.165:0.197 obtained by ICP. Comparative Example 1 has a D50 of 10μm.
[0084] Optionally, a dopant source can be added together with the lithium source in the co-precipitation process of step 1) or the mixing process of step 2. For example, certain elements can be added as dopants to improve the electrochemical properties of the positive electrode active material.
[0085] Example 1 Example 1 is obtained by a solid-state reaction between a lithium source and a transition metal-based source, which is carried out as follows. 1) Coprecipitation: The metal composition Ni was obtained by a coprecipitation process in a large continuous stirred tank reactor (CSTR) containing mixed nickel-manganese-cobalt sulfate, sodium hydroxide, and ammonia. 0.64 Mn 0.17 Co 0.200 A transition metal oxide hydroxide precursor having the formula: 2) Mixing: A transition metal-based oxide hydroxide precursor and LiOH as a lithium source are homogeneously mixed in an industrial blending device with a lithium to metal M' (Li / M') ratio of 1.03 to obtain a mixture. 3) First heating: The mixture from step 2) is heated under oxygen atmosphere at 830° C. for 10 hours. The heated powder is crushed, classified and sieved to obtain an intermediate product. 4) Wet mixing: The following steps 4a) to 4c) are applied to introduce Zr into the positive electrode active material. Step 4a) Preparation of Zr solution: 0.6 mol% Zr from Zr propoxide (70 wt% Zr propoxide in n-propanol solution), 1.2 mol% Li ethoxide powder, and ethanol solvent are mixed to form a solution, based on the total molar content of Ni, Mn, and Co in the intermediate product, respectively. The amount of ethanol solvent is 55 wt% of the total weight of the specified intermediate product to be mixed in step 4b). Step 4b) Mixing: The intermediate product obtained from step 3) is mixed with the Zr solution prepared in step 4a) in a heatable reactor for 20 minutes. Step 4c) Heating: Heat of 70° C. is applied to the reactor of step 4b) while connecting the reactor to a vacuum pump to evaporate the volatile phase. The product obtained from this step is a dry powder. 5) Second Heating: The dried powder from step 4c) is heated at 350°C for 6 hours under oxygen atmosphere to obtain Example 1 with M' containing Ni, Mn, Co and Zr with Ni:Mn:Co:Zr ratio of 0.635:0.163:0.196:0.006 obtained by ICP. Example 1 has D50 of 10μm.
[0086] Comparative Example 2 Comparative Example 2.1 is obtained by the same procedure as Comparative Example 1, except that the first heating temperature in step 3) is 860°C.
[0087] Comparative Example 2.2 is obtained by the same procedure as Example 1, except that the first heating temperature in step 3) is 860°C.
[0088] Comparative Example 3 Comparative Example 3 is obtained by the same procedure as Comparative Example 1, except that the first heating temperature in step 3) is 795°C.
[0089] Example 2 Example 2 is obtained by the same procedure as Example 1, except that the first heating temperature in step 3) is 795°C.
[0090] Comparative Example 4 Comparative Example 4 is obtained by the same procedure as Comparative Example 1, except that the first heating temperature in step 3) is 750°C.
[0091] Example 3 Example 3 is obtained by the same procedure as Example 1, except that the first heating temperature in step 3) is 750°C.
[0092] Comparative Example 5 Comparative Example 5 is obtained by the same procedure as Comparative Example 1, except that the first heating temperature in step 3) is 750°C.
[0093] Example 4 Example 4 is obtained by the same procedure as Example 1, except that the first heating temperature in step 3) is 750°C.
[0094] [Table 4]
[0095] Table 4 summarizes the primary particle diameter, composition and corresponding electrochemical properties of the examples and comparative examples. The average primary particle diameters of Example 1, Example 2, Example 3 and Example 4 are 270, 231, 190 and 192 nm, respectively. These average diameters are smaller than the average primary particle diameter of Comparative Example 2.1 and Comparative Example 2.2, which is 371 nm. The primary particle SEM images of Comparative Example 2.2 and Example 1 are shown in Figure 1b and Figure 1c, respectively. The images include lines and numbers drawn to identify the primary particles to obtain the average primary particle diameter.
[0096] In Table 4, the XPS analysis results of Example 1 and Comparative Example 2.2 show that Ni, Mn, Co and Zr (Zr B The table also compares the results with those of ICP. B indicates that the Zr is present on the surface of the positive electrode active material, in conjunction with the XPS measurements where the signal is obtained from the top of the sample, i.e., the first few nanometers (e.g., 1 nm to 10 nm) of the surface layer. On the other hand, the atomic ratio of Zr obtained from the ICP measurements (ZrA ) is from the whole particle. Therefore, the ratio of XPS to ICP (Zr B / Zr A ) indicates that the element Zr is mainly present on the surface of the positive electrode active material. B / Zr A The Zr value corresponds to more Zr on the surface of the positive electrode active material. B / Zr A is Zr in Comparative Example 2.2 B / Zr A Representative XPS spectra showing the Zr3d5 and 3d3 peaks for Comparative Example 2.2 and Example 1 are shown in FIG.
[0097] 3 shows the TEM-EDS measurement of Example 1 (x-axis: distance from the start of the surface layer at 0, y-axis: elements in atomic ratio). The Zr thickness from the measurement is 25.8 nm.
[0098] The carbon content in the positive electrode active material after Zr treatment was higher than that before treatment, which is related to the better electrochemical performance of the active material. The carbon comes from the Zr alkoxide compound used in the treatment.
[0099] Zr B / Zr A can achieve the object of the present invention to provide a positive electrode active material having an improved first charge capacity of 160 mAh / g or more in a solid-state battery.
Claims
1. A positive electrode active material for a solid-state battery, the positive electrode active material comprising Li, M′, and oxygen, wherein M′ is Ni with a content x of 50.0 mol% to 75.0 mol% relative to M'; Co with a content y of 0.0 mol % to 40.0 mol % relative to M'; Mn with a content z of 0.0 mol % to 40.0 mol % relative to M', D having a content a of 0.0 mol % to 2.0 mol % relative to M', and containing at least one element selected from the group consisting of Al, B, Ba, Ca, Cr, Fe, Mg, Mo, Nb, S, Si, Sr, Ti, Y, V, W and Zn; and Zr having a content b of 0.1 mol % to 5.0 mol % relative to M'; x, y, z, a and b are measured by ICP; x+y+z+a+b is 100.0 mol%, The positive electrode active material has a Zr content defined as b / (x+y+z+b) A The positive electrode active material has a Zr content of Zr B Zr B is determined by XPS analysis, Zr B is expressed as a mole fraction compared to the sum of the mole fractions of Co, Mn, Ni and Zr as determined by XPS analysis; the ratio Zr B / Zr A is 100 or more and 200 or less; The positive electrode active material includes secondary particles having a plurality of primary particles, The primary particles have an average diameter of 170 nm to 340 nm as determined by measuring the primary particle size in an image taken by SEM.
2. The positive electrode active material of claim 1, wherein x≧55.0 mol%.
3. The positive electrode active material according to claim 1 or 2, wherein x≦72.0 mol%.
4. The positive electrode active material according to claim 1 , wherein 0 mol %≦y≦20 mol %.
5. The positive electrode active material according to claim 1 , wherein b is 0.10 mol % or more and 1.00 mol % or less with respect to M′.
6. 6. The positive electrode active material according to claim 1, wherein the median diameter D50 of the secondary particles determined by laser diffraction particle size analysis is 2.0 μm or more and 15.0 μm or less.
7. 7. The cathode active material of claim 1 having a carbon content of 600 ppm or more and 3000 ppm or less as determined by a carbon analyzer.
8. The cathode active material according to claim 1 , wherein the thickness of Zr determined by TEM-EDS measurement is 10 nm or more.
9. A method for producing a positive electrode active material for a solid-state battery, the positive electrode active material being the positive electrode active material according to any one of claims 1 to 8, Preparing a lithium transition metal oxide compound; mixing the lithium transition metal oxide compound with a Zr source to obtain a mixture; heating the mixture at a temperature of 350° C. or more and less than 500° C. in an oxidizing atmosphere in a furnace for a period of 1 hour to 20 hours to obtain a powder of a positive electrode active material.
10. 10. The method of claim 9, further comprising the step of drying the mixture prior to heating the mixture.
11. 10. The method of claim 9, further comprising the step of drying the mixture by vacuum heating prior to heating the mixture.
12. A solid-state battery comprising the positive electrode active material according to claim 1 .
13. 13. The solid-state battery of claim 12, comprising a sulfide-based solid electrolyte containing Li, P and S.
14. 14. Use of the solid-state battery according to claim 12 or 13 in an electric vehicle or a hybrid electric vehicle.
Citation Information
Patent Citations
Positive electrode active material for nonaqueous electrolyte secondary battery and nonaqueous electrolyte secondary battery
JP2004311408A
Positive electrode material for nonaqueous electrolyte secondary batteries, method for manufacturing the same and nonaqueous electrolyte secondary battery
JP2017050204A
Positive electrode active material for all-solid type secondary battery, positive electrode active material layer for all-solid type secondary battery, and all-solid type secondary battery
JP2018120705A
Lithium metal composite oxide powder and positive electrode active material for lithium secondary battery
JP2020172426A
Negative electrode active material for lithium ion secondary cell, method for manufacturing negative electrode active material for lithium ion secondary cell, and lithium ion secondary cell
WO2020027204A1